2020
DOI: 10.1016/j.nmni.2020.100774
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019 re-infection: first report from Turkey

Abstract: There are concerns about the possibility of SARS-CoV-2 reinfection and recently, a patient with SARS-CoV-2 re-infection (or COVID-19) confirmed by epidemiological, clinical, serological and genomic analyses have been published. We have noticed another patient with SARS-CoV-2 re-infection based on clinical and laboratory studies: A 23-year-old woman presented to her hospital with fever (39°C), chills, fatigue, cough, headache, sore throat, muscle and joint pain on April 9, 2020. On examination, oropharynx was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 3 publications
0
24
0
Order By: Relevance
“…Reinfections have been reported internationally since June, 2020, although they remain uncommon. 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 Large longitudinal cohort studies with regular testing are needed to understand the rates of reinfection and their implications for policy by providing systematic epidemiological, virological, immunological, and clinical data. 22 …”
Section: Introductionmentioning
confidence: 99%
“…Reinfections have been reported internationally since June, 2020, although they remain uncommon. 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 Large longitudinal cohort studies with regular testing are needed to understand the rates of reinfection and their implications for policy by providing systematic epidemiological, virological, immunological, and clinical data. 22 …”
Section: Introductionmentioning
confidence: 99%
“…The impact of this high percentage of individuals who lost detectable levels of circulating antibodies on the occurrence of SARS-CoV-2 reinfection remains unknown, as has been reported in some countries [27].…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies have reported that some patients who had recovered from COVID-19 had a positive PCR test result for the second time (5,8,(30)(31)(32)(33)(34)(35)(36). For instance, it was stated in a report that 116 patients in South Korea who had recovered from COVID-19 had positive PCR test results again (33).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it was stated in a report that 116 patients in South Korea who had recovered from COVID-19 had positive PCR test results again (33). In addition, most previously published works which described patients with COVID-19 re-infection were in the format of case reports (5,8,(30)(31)(32)(34)(35)(36) and no studies evaluated the OS and its related predictors among these patients.…”
Section: Discussionmentioning
confidence: 99%